Access to tuberculosis services for individuals with disability in rural Malawi, a qualitative study. - Lisbet Grut; Lifah Sanudi; Stine Hellum Braathen; Thomas Jürgens; Arne H Eide (PLoS ONE, 2015)
Tuberculosis occurs in all populations, but with higher prevalence in poor contexts. Vulnerable groups, including individuals with disability, run a particular risk due to poorer access to information and health services. Studying access to tuberculosis services for vulnerable groups in poor contexts may provide useful insight into the quality of such services in low-income contexts. This article aims to present a contextual understanding of access to tuberculosis services for people with disabilities in one district in southern Malawi. A qualitative method with semi-structured interviews and site observations was applied. In all, 89 participants were interviewed: 47 persons with disability, 11 parents/guardians of youths with disability, and the remaining 31 comprising eight health workers, four community rehabilitation assistants and volunteers, and 19 leaders in the community.Our main findings are that lack of information and knowledge, and considerable confusion related to tuberculosis, its cause and how to protect oneself, are major barrier to accessing services. Disease awareness and personal risk perception are key factors in this regard. Further findings concerns the pathways to tuberculosis related health services, in particular having a test and completing the treatment. The combination of lack of knowledge and barriers in accessing tests implies substantial availability and access problems.It is of importance to understand the combined impact of individual, social, contextual, and systems barriers to fully address the complexity of accessing tuberculosis services for vulnerable groups in poor populations. Lack of disability specific strategies in the local health services may be part of the reason why individuals with disability to not access such services.